The fourfold taxonomy of work-family balance and well-being: the moderating effect of coping strategy / Nurul Nadia Abd Aziz ... [et al.] - Abd Aziz, Nurul Nadia; Abu Yazid, Zaidatul Nadiah; Tarmuji, Nor Habibah; Samsudin, Mawarti Ashik (2016)
The aim of this paper is to investigate the moderating effects of coping strategies on the fourfold taxonomy of work-family balance (WFC, FWC, WFF, and FWF) and well-being among married working women. This paper proposes a conceptual model to examine the relationship between work-family balance and well-being. Besides, this paper also proposes the moderating variable, which is coping strategies that are expected to moderate the relationship between work-family balance and well-being. The findings of this study may provide new conceptualisation related to the influence of these factors on women well-being that may allow for more empirical research to be conducted in the future, in studying the effects on other human resource management aspects.